Boss’s daughters: challenges along the succession process in family business - SILVA, Ivna Pavani (2022)
Family businesses are a large part of the economy, and the succession process is an important aspect of this business arrangement. The founder might observe some characteristics, such as gender and individual traits to elect a successor. Literature has shown that women and particularly daughters might encounter some challenges not only in their election as the successor, but even after they start working in the family business. Per consult on academics’ database, no Brazilian studies were identified with regards to specific daughters approaching succession in family business and their challenges along the succession process. After gathering information from relevant academic sources, the study adopted a qualitative method and data was collected using semi-structured interviews over multiple Brazilian family enterprises to answer the following question: What are the challenges that daughters experience before and during a succession process in a family business? The findings indicate that slowly family businesses are beginning to see daughters as potential successors. Even if they decide to go down another path at an early age, they are being accepted back into the family business. Nevertheless, challenges in relation to work and family conflicts and even some bias from third parties because of being the “boss’s daughter” are the main challenges even after taking over.